Peramalan Stok Penjualan Sahabi Frozen Food dengan Weighted Moving Average - Karim, Muhammad Abdul; Yudatama, Uky; Primadewi, Ardhin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Jajan Sahabi Frozen Food (Jajan Sahabi) is a small and medium-sized enterprise (SME) located in Secang, Magelang, offering various types of frozen foods such as burgers, meatballs, and fries from multiple brands. Currently, inventory tracking at Jajan Sahabi is still conducted manually using a logbook, while stock replenishment is carried out weekly based on the remaining inventory. This approach leads to stock imbalances, either resulting in overstock, which may cause losses, or understock, which could lead to customer dissatisfaction. Forecasting is employed as an alternative decision-making tool to predict product demand based on historical data over a certain period. This study analyzes meatball sales reports from January 2022 to December 2022 using the Weighted Moving Average (WMA) method. The accuracy of the forecasts was evaluated using Mean Absolute Deviation (MAD) and Mean Absolute Percentage Error (MAPE). The forecast results for January 2023 indicate that Meatball Ori is expected to sell 216.3 pieces with a MAD of 76.81 and a MAPE of 53.90%. Meatball Kanzler showed the best performance with a MAPE of 28.80% and a MAD of 28.53. In contrast, Meatball Ikan, Meatball Ikan TL, Meatball Fish dan Shrimp, Meatball Cheese Kanzler, and Meatball Wahid exhibited lower accuracy, with MAPE values ranging from 29.03% to 53.90%. These results suggest that the WMA method produces varying outcomes depending on the product, indicating that further adjustments may be necessary to enhance accuracy.